Meta-analysis on inhibition from childhood to young adulthood in people with Down syndrome. (February 2021) - Fontana, Martina; Usai, Maria Carmen; Toffalini, Enrico; Passolunghi, Maria Chiara
Highlights: People with DS show a small-to-medium deficit on inhibition processes. Matching people with DS and control groups on mental age is of critical importance. Meta-analytic results showed a high amount of heterogeneity among studies. Most studies assessed inhibitory abilities without referring to theoretical models. Abstract: Background: Few studies have investigated inhibition in people with Down syndrome (DS), indicating contradictory results. Aim: This meta-analysis investigated if people with DS show more severe difficulties on inhibition, compared to typically developing (TD) children matched on a measure of mental age (MA). Methods and procedures: Literature search included studies conducted before March 2019, combining the following keywords: "Down syndrome" with "Inhibition", "Interference control", "Effortful control", "Impulsivity", "Self-regulation", and "Executive functions". Descriptive information was coded, according to inclusions criteria. Meta-analysis of standardized differences between DS and TD groups' means was performed. Relevant moderators were also considered. Outcomes and results: Eight studies were included in the meta-analysis, including 161 people with DS and 160 TD children. The results indicated that people with DS showed significantly lower inhibition abilities when they are matched on MA with TD children, instead no significant differences emerged when this matching was not provided. A high heterogeneity across studies was estimated. Conclusions and implications: This meta-analysis indicates that people with DS show, on average, an inhibition deficit compared to TD matched children, albeit not a severe one. These results suggest the importance of investigating in depth inhibition processes in people with DS from childhood to young adulthood.